The extracellular matrix molecule hyaluronic acid regulates hippocampal synaptic plasticity by modulating postsynaptic L-Type Ca2+ channels - Kochlamazashvili, Gaga; Henneberger, Christian; Bukalo, Olena; Dvoretskova, Elena; Senkov, Oleg; Lievens, Patricia M. -J.; Westenbroek, Ruth; Engel, Andreas K.; Catterall, William A.; Rusakov, Dmitri A.; Schachner, Melitta; Dityatev, Alexander (Neuron, 2010)
Although the extracellular matrix plays an important role in regulating use-dependent synaptic plasticity, the underlying molecular mechanisms are poorly understood. Here we examined the synaptic function of hyaluronic acid (HA), a major component of the extracellular matrix. Enzymatic removal of HA with hyaluronidase reduced nifedipine-sensitive whole-cell Ca2+ currents, decreased Ca2+ transients mediated by L-type voltage-dependent Ca2+ channels (L-VDCCs) in postsynaptic dendritic shafts and spines, and abolished an L-VDCC-dependent component of long-term potentiation (LTP) at the CA3-CA1 synapses in the hippocampus. Adding exogenous HA, either by bath perfusion or via local delivery near recorded synapses, completely rescued this LTP component. In a heterologous expression system, exogenous HA rapidly increased currents mediated by Cav1.2, but not Cav1.3, subunit-containing L-VDCCs, whereas intrahippocampal injection of hyaluronidase impaired contextual fear conditioning. Our observations unveil a previously unrecognized mechanism by which the perisynaptic extracellular matrix influences use-dependent synaptic plasticity through regulation of dendritic Ca2+ channels.
In Titel erscheinen die Zeichen 2+ in der chemischen Formel hochgestellt
Gesehen am 16.03.2023